REINTERPRETASI ISTILAH ‘EZER’ (עֵזֶר) DALAM KEJADIAN 2:18: MENEMUKAN IDENTITAS PEREMPUAN SEBAGAI CERMIN ILAHI DALAM PERSPEKTIF TEOLOGI FEMINISME - Susi Cicilya Surati Surati (PT. Giat Konseling Nusantara, 2025)
This article reinterprets the term ezer kenegdo in Genesis 2:18 through Hebrew linguistic analysis, feminist critical reading, and contextual theological reflection. Traditionally, ezer kenegdo has been interpreted in patriarchal frameworks as referring to a subordinate “helper.” However, linguistically, ezer refers to God's powerful and salvific help, while kenegdo implies equality and mutuality. Employing a feminist lens, the article reveals that women in the creation narrative are not portrayed as subordinate but as equal and spiritual partners. More significantly, women are understood as divine mirrors, reflecting God’s attributes in creation and life. The article calls for the deconstruction of patriarchal interpretations and offers a new paradigm for a gender-just, contextual, and liberating Christian theology.